(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Climate defines the viability of an area for aquaculture at the macro-scale (extensive) level as it dictates water temperature and water quantity in a location that in turn affects fish productivity. Temperature and rainfall data from 1980 to 2016 were analyzed and compared among the different regions of Uganda (Central, Eastern, Northern, and Western) using the Seasonal Mann Kendall Times Series and the 12-month Standard Precipitation Index (SPI). These data were used in the computation of monthly water requirements of the different regions. A positive upward temperature trend for all regions except the Eastern region (p = 0.4222, tau b = 0.027) showed increase of aquaculture production the future. The 12-month SPI showed all regions having near normal SPI (-0.99 to 0.99) but with the Central region having highest SPI and the western region with the lowest SPI. The Central region had the lowest monthly water requirement compared to other regions which was attributed to lower temperatures and lower evaporation rates compared to others. Overall, potential climate effects on aquaculture are not a major issue in the country if climate smart strategies are adopted. That is; water harvesting during the rainy seasons for use in drier periods and planning of the fish production cycle so that the period of water deficit coincides with fish harvest or pond preparation.